2007
DOI: 10.1158/1078-0432.ccr-07-0403
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial of Single-Dose Intrapleural IFN-β Gene Transfer for Malignant Pleural Mesothelioma and Metastatic Pleural Effusions: High Rate of Antitumor Immune Responses

Abstract: Purpose: This phase 1 dose escalation study evaluated the safety and feasibility of single-dose intrapleural IFN-β gene transfer using an adenoviral vector (Ad.IFN-β) in patients with malignant pleural mesothelioma (MPM) and metastatic pleural effusions (MPE). Experimental Design: Ad.IFN-β was administered through an indwelling pleural catheter in doses ranging from 9 × 1011 to 3 × 1012 viral particles (vp) in two cohorts of patients with MPM (7 patients) and MPE (3 patients). Subjects were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 43 publications
4
142
0
2
Order By: Relevance
“…CAR T cells have been shown to be a promising T-cell-based immunotherapy in leukemia (25,26,29,52,53). CAR T cells targeting CD19 have resulted in sustained complete responses and shown complete response rates of ≈90% in patients with relapsed or refractory acute lymphoblastic leukemia (54).…”
Section: Discussionmentioning
confidence: 99%
“…CAR T cells have been shown to be a promising T-cell-based immunotherapy in leukemia (25,26,29,52,53). CAR T cells targeting CD19 have resulted in sustained complete responses and shown complete response rates of ≈90% in patients with relapsed or refractory acute lymphoblastic leukemia (54).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that only about 11% of clinical mesothelioma cases are confined to the peritoneum , the model is also considered a well-accepted surrogate for the more common pleural mesothelioma. Although some MM studies have shown promise for localised intraperitoneal and intrapleural administration of chemotherapeutics (Hotta et al, 2004;Sterman et al, 2007), most trials have been inconclusive. Localised administration of EGF4KDEL may offer advantages in lower systemic toxicity, eased immune response, and greater tumour targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has been conducting preclinical and clinical trials for mesothelioma tumors with a nonreplicating adenoviral vector expressing human IFN-b (Odaka et al, 2002;Sterman et al, 2007). We have seen strong antitumor effects that are mediated primarily through virus-induced inflammation in combination with tumor cell secretion of IFN-b that leads to both innate and acquired immune-mediated antitumor responses.…”
Section: Introductionmentioning
confidence: 99%